2018
DOI: 10.3892/ol.2018.9685
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression in pediatric intracranial ependymomas and their potential value for tumor grading

Abstract: Intracranial ependymoma represents one of the most common pediatric central nervous system malignancies, and exhibits a wide range of clinical behavior from relatively indolent lesions to highly malignant anaplastic ependymomas. Due to the heterogeneous nature of this disease there is lack of prognostic markers, which would reliably predict the outcome of patients. MicroRNAs (miRNAs) have emerged as important molecules in cancer biology during past decade; however, very little is known about their role in epen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Another study also identified that the miR-135a-3p, miR-137, miR-17-5p, miR-181d, and let-7d-5p were upregulated in EPNs. 156 Low expression of miR-10a and high expression of miR-10b and miR-29a in EPN were also validated by qRT-PCR. 157 …”
Section: Epnmentioning
confidence: 87%
See 1 more Smart Citation
“…Another study also identified that the miR-135a-3p, miR-137, miR-17-5p, miR-181d, and let-7d-5p were upregulated in EPNs. 156 Low expression of miR-10a and high expression of miR-10b and miR-29a in EPN were also validated by qRT-PCR. 157 …”
Section: Epnmentioning
confidence: 87%
“…Specifically, miR-17-5p, miR-19a-3p, miR-106b-5p, miR-124-3p, and miR-203a were shown to be differentially expressed between grade II and III EPNs. 156 , 158 , 159 These miRNAs were overexpressed in posterior fossa EPNs, including miR-106-b-5p and miR-19a-3p. 158 Moreover, miR-203, miR-17-5p, miR-124-3p, miR-192-5p, miR-221-3p, miR-222-3p, miR-326, miR-371a-5p, and miR-520g-3p were significantly correlated with tumor relapse.…”
Section: Epnmentioning
confidence: 98%
“…Both miR‐135a‐3p and miR‐4476 were reported to be upregulated miRNAs that promote cell proliferation, migration, and invasion in CNS tumors. 34 , 35 Further mechanistic analyses indicated that adenomatous polyposis coli, a negative regulator of the Wnt/β‐catenin signaling pathway, is a direct target of miR‐4476 and mediates the oncogenic effect of miR‐4476 in glioma. 35 This may explain high concentrations of these two miRNAs in DLBCL cases.…”
Section: Discussionmentioning
confidence: 99%
“…Both of miR-135a-3p and miR-4476 were reported as upregulated miRNAs that promoted cell proliferation, migration and invasion in CNS tumors (37,38). Further mechanistic analyses indicated the adenomatous polyposis coli(APC), a negative regulator of the Wnt/β-catenin signaling pathway, is a direct target of miR-4476 and mediated the oncogenic effect of miR-4476 in glioma (38).…”
Section: Discussionmentioning
confidence: 99%